FACTORS OF INCREASING COMPETITIVENESS IN LIGHT INDUSTRY - Saidmuradova T. S.; Shokirova D. J. (Ecominds Press, 2025)
This article presents the role of the textile industry in our country, the competitiveness of textile products and the factors affecting it, the current production volume of the textile industry of our country, export activities and export geography.
Keywords: Textile industry, competitiveness, export, export geography, quality management, human resources, innovative technologies.